2019
DOI: 10.1002/jcph.1408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Oxycodone Versus Sufentanil on the Incidence of Postoperative Nausea and Vomiting in Patients Undergoing Gynecological Laparoscopic Surgery

Abstract: More than 30% of patients who undergo surgery will experience postoperative nausea and vomiting (PONV) if no prophylactic treatments are used. Although numerous studies have been performed to investigate the factors related to PONV, the effect of perioperative intravenous oxycodone on the incidence of PONV has not been well investigated. In this study, gynecological patients (grade I-II, aged 18-65 years, scheduled to undergo elective gynecological laparoscopic surgery under general anesthesia) were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Tao et al . 67 reported that the incidence of PONV in gynecological patients who underwent laparoscopic surgery was lower when using intraoperative and postoperative intravenous (IV) oxycodone compared to IV sufentanil. However, Han et al .…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…Tao et al . 67 reported that the incidence of PONV in gynecological patients who underwent laparoscopic surgery was lower when using intraoperative and postoperative intravenous (IV) oxycodone compared to IV sufentanil. However, Han et al .…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…Nevertheless, PONV were still observed in patients in all groups, and the incidence rate of PONV was more than 20% 24 hours after surgery, which is similar to previous studies. 31,32 However, patients with sufentanil PCIA showed higher incidence rate of PONV when compared with patients with oxycodone PCIA 24 and 48 hours after surgery, demonstrating the advantages of oxycodone over sufentanil in postoperative pain relief. Respiratory depression is one of the most concerned anesthesia-related adverse complications after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Pain is one of the major factors limiting early mobilization after hip surgery, resulting increased risks of thromboembolism and infection, or delayed postoperative rehabilitation, especially for the elderly patient [9,10]. Appropriate pain management is crucial, and there are several choices of techniques for postoperative analgesia including epidural block, peripheral nerve block, transdermal administration, and intravenous analgesics infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Considering an estimated 20% dropout rate, 165 subjects in each group, and a total of 330 subjects are required. For the primary outcome of incidence of PONV, it is reported to be 38.8% in sufentanil and 25.3% in oxycodone [9]. Assuming the difference between two groups at a 2.5% significance level and a power of 0.80, 223 subjects are required in each group.…”
Section: Methods/design Trial Designmentioning
confidence: 99%